Effects of feeding in free-range conditions or in confinement with different dietary MUFA/PUFA ratios and α-tocopheryl acetate, on antioxidants accumulation and oxidative stability in Iberian pigs. - Daza, a; Rey, a I; Ruiz, J; López-Bote, C J (Meat science, 2005)
The experiment was undertaken to provide information of the influence of feeding either free-range or in confinement with different dietary MUFA/PUFA ratios and α-tocopheryl acetate supplementation (40 vs. 200 mg/kg) on tocopherol content and susceptibility to lipid oxidation of muscle and microsomes in Iberian pigs. The grass provided to the pigs had a similar α-tocopherol concentration to that observed for diets supplemented with 200 mg/kg α-tocopheryl acetate, and acorns supplied fourfold higher content of γ-tocopherol than the experimental diets. The α- and γ-tocopherol contents of muscle reflected the tocopherol concentration of the diets. Mono and Medium diets produced a similar MUFA/PUFA ratio in neutral and polar lipids of pig muscle to those fed outdoors. The lowest TBARS numbers were found in muscle samples from pigs fed a MUFA-enriched diet in confinement. No significant influence of free-range feeding or dietary fat on drip loss was found. However, α-tocopheryl acetate supplementation reduced (P<0.05) drip loss. Dietary vitamin E supplementation decreased the membrane lipid oxidation by 18% after 120 min. However, free-range feeding decreased the extent of microsome oxidation by 20%, 56% and 82% after 120 min when compared with those groups fed in confinement with high, medium and low MUFA/PUFA ratios, respectively. The hexanal concentration of muscle showed a similar trend to that observed for microsome induced-oxidation, suggesting, that hexanal determination is a more accurate method to measure lipid oxidation in iberian pig muscle than the thiobarbituric acid test.
Keywords: a- and c-tocopherols; dietary fat; free-range feeding; lipid oxidation; microsomes

Effects of feeding in free-range conditions or in confinement with different dietary MUFA/PUFA ratios and α-tocopheryl acetate, on antioxidants accumulation and oxidative stability in Iberian pigs. - Daza, a; Rey, a I.; Ruiz, J.; López-Bote, C. J. (Meat science, 2005)
The experiment was undertaken to provide information of the influence of feeding either free-range or in confinement with different dietary MUFA/PUFA ratios and α-tocopheryl acetate supplementation (40 vs. 200 mg/kg) on tocopherol content and susceptibility to lipid oxidation of muscle and microsomes in Iberian pigs. The grass provided to the pigs had a similar α-tocopherol concentration to that observed for diets supplemented with 200 mg/kg α-tocopheryl acetate, and acorns supplied fourfold higher content of γ-tocopherol than the experimental diets. The α- and γ-tocopherol contents of muscle reflected the tocopherol concentration of the diets. Mono and Medium diets produced a similar MUFA/PUFA ratio in neutral and polar lipids of pig muscle to those fed outdoors. The lowest TBARS numbers were found in muscle samples from pigs fed a MUFA-enriched diet in confinement. No significant influence of free-range feeding or dietary fat on drip loss was found. However, α-tocopheryl acetate supplementation reduced (P<0.05) drip loss. Dietary vitamin E supplementation decreased the membrane lipid oxidation by 18% after 120 min. However, free-range feeding decreased the extent of microsome oxidation by 20%, 56% and 82% after 120 min when compared with those groups fed in confinement with high, medium and low MUFA/PUFA ratios, respectively. The hexanal concentration of muscle showed a similar trend to that observed for microsome induced-oxidation, suggesting, that hexanal determination is a more accurate method to measure lipid oxidation in iberian pig muscle than the thiobarbituric acid test.
The following values have no corresponding Zotero field: accession-num: 22062651
Keywords: a- and c-tocopherols; dietary fat; free-range feeding; lipid oxidation; microsomes